Islamic relationship marketing practice, customer satisfaction, and retention: a mediation analysis - Che Mohd Salleh, Marhanum (INSI Publications, 2014)

(untitled)
The aim of this study is to develop an indirect effect of customer satisfaction towards the structural relationship of the Takaful agents’ Islamic relationship marketing (IRM) practice and future customer retention. The model was designed and later examined by utilizing the Structural Equation Modelling (SEM) procedure on data collected from a survey of Malaysian Takaful customers that yielded 755 usable questionnaires. The results confirmed that customer satisfaction has significantly mediated the four measures of IRM which were Islamic ethical behaviour, social, structural, and financial bonds on future customer retention. It is vital to do the empirical study utilizing primary data on the perspective of customers as to observe the real practice of marketing in the Takaful industry in Malaysia. The findings imply that the practice of Islamic relationship marketing is very crucial to ensure the sustainable of future Takaful industry which at the end would affect the bright future of the industry. Therefore, the industry needs to ensure their marketing channel practicing the IRM towards achieving customer satisfaction and retention. This research is one of the first known attempts to use SEM to test a mediation effect particularly on the IRM practice in the industry.